Malaysia Airport Holdings Bhd : Strategies For Becoming Profitable - Singaram, Muthupalaniappan (2003)
Malaysia Aiport Holdings Bhd (MAHB) manages and operates a total of 37 airports in Malaysia except for Kerteh airport in Terengganu; the Group manages and operates all the commercial airports in Malaysia. MAHB's function in operating airports includes the development, management and maintenance of existing terminal buildings, runways, roads, car parks, placing primary importance on operational efficiency, safety and security of passengers and aircraft and fulfillment of environment requirements.